Facial anatomy applied to live models - Ricardo Frota Boggio; Agnaldo Gonçalves de Castro; Kazuyo Yamada; Adriane Tartare; Daniel Boro dos Santos; Gladstone Eustáquio de Lima Faria (Revista Brasileira de Cirurgia Plástica)
Introduction: Anatomy is one of the foundations in medicine, and choosing a practical and dynamic teaching method is essential for better retention of your learning. The objective is to use facial anatomy applied to live models as an innovative teaching strategy and to evaluate the experience of the learning experience of students assigned to the method. Method: The work analyzes the experience with body painting of 51 students from Instituto Boggio assigned this method (or instructed to use this method) during their classes. Different planes and anatomical structures were represented on live models’ faces to simulate and teach the main injectable cosmetic procedures; syringes, needles, cannulas, and ultrasound gel stained with food inks were used. Overlapping latex layers were used for the anatomical study of the temple, middle third of the face, and nose, allowing the reproduction of fillers and biostimulators in these regions. The main muscle groups were represented for the discussion of high-precision botulinum toxin. After the entire demonstration, the students answered a questionnaire via “Google Forms” evaluating the methodology used. Results: According to the answers to the questionnaires, most students considered body painting an innovative methodology that contributed to learning anatomical content and satisfactorily illustrating the demonstrated cosmetic procedures. Conclusion: Practical learning through live models makes this new teaching method something innovative and unique that, in an enjoyable way, enables the study of anatomy and appropriately trains clinical skills.